Can Good Economics Ever Be Good Politics? : Case Study of India's Power Sector. - Lal, Sumir, 1961- (World Bank working paper, 2006)
In recent years, the power sector in several developing countries has suffered from a frustrating gap between strong, pro-reform rhetoric at the political level, and weak, hesitant implementation of the reform measures on the ground. Focusing on the recent experience of power sector reform in India, this paper looks afresh at the problem of the "rhetoric-implementation gap" by taking the lack of political will as its starting point, and identifying the ingredients that comprise it in the current context of India. Assuming that people and institutions are not impartial but instead respond to po